Training Highly Qualified Health Research Personnel: The Pain in Child Health Consortium - Carl L von Baeyer; Bonnie J Stevens; Christine T Chambers; Kenneth D Craig; G Allen Finley; Ruth E Grunau; C Celeste Johnston; Rebecca Pillai Riddell; Jennifer N Stinson; Justine Dol; Marsha Campbell-Yeo; Patrick J McGrath (Pain Research and Management)
BACKGROUND AND OBJECTIVES: Pain in Child Health (PICH) is a transdisciplinary, international research training consortium. PICH has been funded since 2002 as a Strategic Training Initiative in Health Research of the Canadian Institutes of Health Research, with contributions from other funding partners and the founding participation of five Canadian universities. The goal of PICH has been to create a community of scholars in pediatric pain to improve child health outcomes.